Hybrid intermediaries - Nicola Cetorelli (Federal Reserve Bank of New York, 2014)
I introduce the concept of hybrid intermediaries: financial conglomerates that control a multiplicity of entity types active in the "assembly line" process of modern financial intermediation, a system that has become known as shadow banking. The complex bank holding companies of today are the best example of hybrid intermediaries, but I argue that financial firms from the "nonbank" space can just as easily evolve into conglomerates with similar organizational structure, thus acquiring the capability to engage in financial intermediation. I document instances of the emergence and growth of such nonbank hybrid intermediaries. Notable nonbank firms (for example, from the investment banking or specialty lending sectors) that had become significant intermediaries and that turned into bank holding companies post-Lehman are, from an organizational standpoint, indistinguishable from firms with a traditional banking origin. Similar inference can be drawn by analyzing specific activities. I focus on securities lending, a well-understood example of shadow financial intermediation, and document the emergence of a firm from the asset management sector as one of the largest providers of related intermediation services globally.
Keywords: G20; L20; 330; intermediation; conglomeration